THE DILEMMA OF POLITICAL EDUCATION AS A TRANSFORMATION BASIS OF JEMAAH TARBIYAH MOVEMENT - Nasiwan Nasiwan (Millah: Journal of Religious Studies, 2014)
This research aims at finding out the dilemma occurring in the political education, performed by the organization named Gerakan Jemaah Tarbiyah. A qualitative approach by critical analysis was employed, and the data was gathered by documented and in depth interview methods. The result explained that; first, political education in a phase of the missionary movement could influence Jemaah Tarbiyah in transforming the movement by transmitting various knowledge, attitude and political awareness that Jemaah Tarbiyah had. Second, there was a political education trend which already shifted the roles as the indoctrination instruments for the party to transmit values and justifier various policies decided by the elite of the party.